Leopard population density, home range size and movement patterns in a mixed landuse area of the Mangwe District of Zimbabwe - Grant, Tanith-Leigh (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2012)
Trophy hunting is often employed as a conservation management tool for large predators. However, in order for this method to succeed, hunting levels must be sustainable. Very little robust population data exist for African leopards (Panthera pardus) in general, and almost no density or spatial ecology data exist for leopards in Zimbabwe. Zimbabwe has one of the highest annual CITES leopard trophy hunting quotas in Africa, the sustainability of which has not been assessed, despite large scale landuse changes over the last 12 years. The focal area of this study was within the Mangwe district, in the south-west of Zimbabwe. The region is dominated by cattle and wildlife ranches, with high levels of leopard hunting, making it an important area for assessing leopard population density and spatial ecology. Three population density estimation methods were employed in my study: a spoor index survey, an unbaited camera-trapping survey and a baited camera-trapping survey. Using three calibration equations, spoor indices appeared to underestimate the leopard population (1.28-3.29 leopards/ 100 km²) as the equations were calibrated for areas with different habitats and leopard densities. In addition, the unbaited camera survey only produced six leopard photographs, unsuitable for individual identification and analysis. By contrast, the baited camera survey produced 292 identifiable leopard photographs, from which 13 individuals were identified. Density estimates calculated using the programme CAPTURE and the M[subscript]h model with the Mean Maximum Distance Moved Outside of Study Area (MMDMOSA) buffer method (4.79±0.83 leopards/100 km²), and the programme SPACECAP, using a buffer of 2.5 km (5.12±0.62 leopards/100 km²), appeared to generate the most reliable leopard population estimates. To assess the spatial ecology, three leopards (one male, two females) were captured and fitted with GPS collars. The home range estimates of the three leopards (95% Kernel UD: male 263 km², females 31 and 45 km²) were smaller than those of leopards in more arid regions, but larger than those of mesic habitats. This suggests that the Mangwe area has a higher quality habitat than the arid regions of Namibia, but less suitable habitat than protected bushveld areas (e.g. Kruger National Park, South Africa). My data represents the first robust leopard density and home range assessment for Zimbabwe. In addition, my results indicate that the current hunting quota issued to the Mangwe area is unsustainable. Consequently, I recommend revising the quota to five leopards for the entire area, and halving the current national leopard quota to 250, until a national leopard census is completed.
Keywords: Leopard -- Monitoring -- Zimbabwe; Leopard -- Conservation -- Zimbabwe; Wildlife monitoring -- Zimbabwe; Wildlife conservation -- Zimbabwe